(untitled) (Circe de clásicos y modernos, 2026)
The objective of this research is twofold: 1) to demonstrate, through the recording and analysis of On the Indestructibility of the World, paragraph by paragraph, that it is not authentically authored by Philo of Alexandria, especially since the greater part of it is a quotation from other authors of antiquity; 2) to demonstrate the danger of modern doxography that collects –as Von Arnim does in Stoicorum Vetera Fragmenta– unique and independent testimonies –such as these that are only recorded in Aet. within the framework of an anti-Stoic diatribe– and disseminates them as reliable testimonies from specific authors.